A VTST Study of the H + O3 and O + HO2 Reactions Using a Six-dimensional DMBE Potential Energy Surface for Ground State HO3 - Fernández-Ramos, A. (2002)
The variational transition state theory (VTST) is used to calculate thermal rate constants for the reactions H + O3 → OH + O2 (R1) and O + HO2 → OH + O2 (R2). Both reactions are studied using a double many-body expansion (DMBE) potential energy surface for ground state HO3. The VTST results are compared with quasiclassical trajectory calculations (QCT) and experiment. Reaction R1 shows a planar transition state which, including the zero-point energy, is 0.16 kcal mol-1 above the reactants. This reaction presents two maxima in the vibrational adiabatic potential, and hence, unified statistical theory in its canonical (CUS) and microcanonical (US) versions has been employed in addition to the canonical (CVT) and microcanonical (μVT) variational transition state theories. The results obtained by the CUS and US methods compare well with QCT and experiment. The DMBE potential energy surface predicts that reaction R2 occurs via oxygen abstraction. Two possible reaction paths were found for this reaction. One path has no transition state with an oxygen angle of attack close to 155°, and the other path presents a transition state with an oxygen angle of attack of about 80°. Because the potential energy surface for this reaction is quite flat, the CVT and μVT methods were used together with an algorithm that reorients the dividing surface to maximize the Gibbs free energy. The VTST results are found to agree reasonably well with experiment and with QCT calculations.